Synthesis of deuterium-labelled amlexanox and its metabolic stability against mouse, rat and human microsomes - Gan, Xinmin (J Labelled Comp Radiopharm, 2019)
As part of a program toward making analogues of amlexanox (1), currently under clinical investigation for the treatment of type 2 diabetes and obesity, we have synthesized derivative 5 in which deuterium has been introduced into two sites of metabolism on the C-7 isopropyl function of amlexanox. The synthesis of 5 was completed in an efficient three-step process utilizing reduction of key olefin 7b to 8 by Wilkinson’s catalyst to provide specific incorporation of di-deuterium across the double bond. Compound 5 displayed nearly equivalent potency to amlexanox (IC(50) 1.1 μM vs 0.6 μM, respectively) against recombinant human TBK1. When incubated with human, rat, and mouse liver microsomes, amlexanox (1) and d(2)-amlexanox (5) were stable (t(1/2) > 60 min) with 1 showing marginally greater stability relative to 5 except for rat liver microsomes. These data show that incorporating deuterium into two sites of metabolism does not majorly suppress Cyp-mediated metabolism relative to amlexanox.